Analysis of Divorce Decision on Legal Responsibility and Divorce Procedure in Decision No. 251 / Pdt.G / 2025 / PN Mdn - Maswandi, Maswandi (International Asia Of Law and Money Laundering (IAML), 2025)
This study aims to analyze the legal considerations of judges in Decision No. 251 / Pdt.G / 2025 / PN Mdn which is a divorce case decided by the Medan District Court in 2025. Using a normative juridical approach, this study examines the suitability of divorce procedures with applicable legal provisions, as well as analyzing the legal consequences of the judgment against the parties. The findings showed that the court had carried out procedures in accordance with the code of civil procedure, including mediation efforts and summons of the parties. This decision is important as a precedent in assessing the effectiveness of domestic dispute resolution mechanisms in the General Court.